Respuesta :

Answer:

6x² - 2x - 6

Step-by-step explanation:

Note that (f - g)(x) = f(x) - g(x)

f(x) - g(x) = 6x² - 4 - (2x + 2) = 6x² - 4 - 2x - 2 = 6x² - 2x - 6

Answer:

[tex](f-g)(x)=6x^{2}-2x-6[/tex]

Step-by-step explanation:

1) Given two functions f(x) and g(x) we can operate them like this:

[tex]f(x)+g(x)=(f+g)(x)\\f(x)-g(x)=(f-g)(x)\\f(x)*g(x)=(f*g)(x)\\f(x):g(x)=\frac{f(x)}{g(x)}[/tex]

In this question the point is subtracting them, so:

2)

[tex]}\\\\f(x)=6x^{2}-4\, \:\:g(x)=2x+2\Rightarrow (f-g)(x)=6x^{2}-4-(2x+2)\Rightarrow (f-g)(x)=6x^{2}-4-2x-2\Rightarrow (f-g)(x)=6x^{2}-2x-6[/tex]

This function has a Domain, as a polynomial function:

[tex]D=\left ( -\infty, +\right )[/tex]

And an Range =

[tex]R=[\frac{-37}{6},\infty)[/tex]

Ver imagen profantoniofonte
ACCESS MORE